Penerapan Pengelolaan Keuangan Desa Berdasarkan Permendagri Nomor 113 Tahun 2014 di Desa Pugul Kabupaten Bangka - Fikri, Zakiyudin; Ramadhona, Rizky; Marleni, Marleni (Jurnal Publisitas, 2023)
This research is one of the studies presented to look at the implementation of village financial management based on Permendagri number 113 of 2014. This research was conducted on one of the objects, namely Pugul Village, Riau Silip District. This research uses a descriptive qualitative research method. In this type, researchers will be more flexible in explaining in detail how the process of managing village finances in Pugul Village. Data collection uses three data sources, namely interviews, observation and documentation. The analysis in this study uses qualitative analysis techniques with three stages including: data reduction, delivery of analysis results and drawing conclusions. The results of this study are that in general the stages in the financial management of Pugul Village are in accordance with Permendagri Number 113 of 2014. However, there are still several stages that are still not appropriate, namely the Draft Village Regulation on APBDesa is mutually agreed upon no later than October of the current year. However, Pugul Village experienced delays because there were new regulations that required time to adjust the APBDes.